Update on pediatric heart transplantation. Long-term complications. - Gajarski, R J (1997)
Despite evolution to "higher-order" immunosuppressive agents that better control cell-mediated allograft rejection and, therefore, short- and intermediate-term survival, allograft vasculopathy and PTLD remain factors that limit extended graft survival. While improved basic science "bench" techniques have enabled investigation of their pathogenesis at the subcellular and molecular levels, each scientific advance leads the way to the next horizon of complex questions. Only through a more complete understanding of the etiology and pathophysiology of these processes will we be able to design strategies to combat these complications.